Mid-infrared photonics and optoelectronics in 2D materials - Liang, Guozhen (2022)
With intriguing properties that are different from the conventional bulk materials, two-dimensional (2D) materials have attracted numerous and widespread research interests, including its applications in photonics and optoelectronics. Devices based on 2D materials have been demonstrated in a wide spectral range, from the ultraviolet to the terahertz, and the microwave wavelength range. The mid-infrared (MIR) region (about 2–20 μm) bears a particular scientific and technological significance because, for instance, many molecules have their spectral fingerprints and there are atmosphere transparent windows in this region. Nevertheless, the MIR region remains underdeveloped compared to the visible and the near-infrared telecommunication regimes, mainly due to the lack of suitable materials, such as narrow bandgap materials, and proper photonic designs for building high performance optoelectronic devices in this wavelength regime. Therefore, researchers have been exploring the possibility and opportunity of 2D materials to fill up the gap. Here, we review the key recent developments of 2D materials in the MIR photonic and optoelectronic applications, including photodetection, light modulation, surface plasmon polaritons, phonon polaritons, and their nonlinearities and provide an outlook on the challenges and opportunities that lie ahead for MIR optoelectronic research fields with 2D materials.